2018
DOI: 10.1002/ejp.1246
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of sympathetic sprouting in CCD rats by lacosamide

Abstract: Early LCM administration inhibited sympathetic sprouting within DRG in CCD rats via reducing hyperexcitability of neurons. Early LCM administration suppressed neuropathic pain in CCD rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…In other pain models we and others have observed that, as in this study, any manipulation that reduces abnormal spontaneous activity of sensory neurons improves pain behaviors (Devor M, 2009;Xie W, Strong JA, Kim D, Shahrestani S and Zhang JM, 2012;Xie W et al, 2009;Xie W, Strong JA and Zhang JM, 2015;Xie W, Tan ZY, Barbosa C, Strong JA, Cummins TR and Zhang J-M, 2016). In the CCD model, drugs that blocked spontaneous activity or targeted sodium channels while improving pain behaviors include thiamine, (Song XS, Huang ZJ and Song XJ, 2009) local bupivacaine nanoparticles, (Wang T et al, 2018) and lacosamide (Wang Y and Huo F, 2018). The spontaneous activity we observed was predominantly in cells with action potential durations <1.5 msec; these were likely predominantly cells with myelinated axons based on a subset of cells with measured conduction velocities.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In other pain models we and others have observed that, as in this study, any manipulation that reduces abnormal spontaneous activity of sensory neurons improves pain behaviors (Devor M, 2009;Xie W, Strong JA, Kim D, Shahrestani S and Zhang JM, 2012;Xie W et al, 2009;Xie W, Strong JA and Zhang JM, 2015;Xie W, Tan ZY, Barbosa C, Strong JA, Cummins TR and Zhang J-M, 2016). In the CCD model, drugs that blocked spontaneous activity or targeted sodium channels while improving pain behaviors include thiamine, (Song XS, Huang ZJ and Song XJ, 2009) local bupivacaine nanoparticles, (Wang T et al, 2018) and lacosamide (Wang Y and Huo F, 2018). The spontaneous activity we observed was predominantly in cells with action potential durations <1.5 msec; these were likely predominantly cells with myelinated axons based on a subset of cells with measured conduction velocities.…”
Section: Discussionsupporting
confidence: 57%
“…Both CCD and LID models induce sympathetic sprouting in the DRG (Chien SQ et al, 2005;Xie WR, Deng H, Li H, Bowen TL, Strong JA and Zhang J-M, 2006). After CCD, sensory neurons may develop increased sensitivity to adrenergic and other sympathetic transmitters such as neuropeptide Y; conversely, blocking Na channels may have improved pain in part by reducing sympathetic sprouting (Wang Y and Huo F, 2018;Xie W et al, 2011;Zhang J-M et al, 2004). However, it is difficult to attribute all the behavioral effects of Na channel knockdown in our study to reduction of sympathetic sprouting into the DRG, as the behavioral effects were marked even on POD 1 while sympathetic sprouting develops more slowly (Chien SQ, Li C, Li H, Xie W, Pablo CS and Zhang JM, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We tested the MWT of rats at different time points. The results showed that continuous compression of DRG significantly reduced the MWT of the hind paw and was consistent with previous studies [27,28], as shown in Figure 1(b). The MWT decreased significantly on the first day after CCD and reached the lowest point on the 7th day (P < 0:0001).…”
Section: Induction and Persistence Of Allodynia In Ccd Modelsupporting
confidence: 92%
“…Synapse-like structures made by sympathetic fibers and dendrites were proved to contribute to the maintenance of chronic pain state [18]. The reduced sprouting produced by early fiber blockage decreased the spontaneous activity of DRG neurons and pain behaviors [43][44][45]. All the previous results were achieved from adult neuropathic pain models.…”
Section: Discussionmentioning
confidence: 95%
“…The sprouting fibers preferentially formed nests with synapse-like structures around the spontaneously active neurons or tangled with efferent fibers [18,42]. The number of sprouting fibers had been proved statistically correlated with neuropathic behaviors [16,43]. Synapse-like structures made by sympathetic fibers and dendrites were proved to contribute to the maintenance of chronic pain state [18].…”
Section: Discussionmentioning
confidence: 99%